Evaluation of healing in feline femoral defects filled with cancellous autograft, cancellous allograft or Bioglass - Dorea, H. C.; McLaughlin, R. M.; Cantwell, H. D.; Read, R.; Armbrust, L.; Pool, R.; Roush, J. K.; Boyle, C. (Veterinary and Comparative Orthopaedics and Traumatology, 2005)
Cancellous bone grafting is a widely accepted technique in human and veterinary orthopaedic surgery. However, the use of autogenous bone graft is limited by the additional surgical time required to harvest the graft, the morbidity associated with the donor site, and the limited availability of cancellous bone, especially in feline patients. Various allografts and bone graft substitutes are available commercially but have not been fully evaluated for efficacy in the cat. The purpose of this study was to compare the incorporation of autogenous and allogenous cancellous bone graft and Bioglass®, a synthetic bone graft substitute, in femoral defects in cats. Four (4.0 mm diameter) defects were created in the lateral diaphyseal cortex of the left femur with an orthopaedic drill. In each femur, one of the cortical defects was filled with autogenous cancellous graft (harvested from the tibia), one was filled with allogenic cancellous graft, and one was filled with Bioglass. The fourth defect remained unfilled. Graft incorporation within the femoral defects was evaluated by radiographic evaluation every two weeks. Six weeks after the grafting procedure, the cats were euthanatized and high detailed radiography, dual energy X-ray absorptiometry (DEXA), histopathology and histomorphometry of the defects were performed. Satisfactory bone healing was observed within all of the defects.
Keywords: Bone grafts; cancellous autograft; cancellous allograft; Bioglass®; feline